PERPUSTAKAAN ISLAM CORDOBA: KIBLAT PERADABAN ILMU PENGETAHUAN DI ERA DINASTI BANI UMAYYAH II 961-976 M - Rahmat Iqbal; Agus Mahfudin Setiawan (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2024)
The Islamic Library in Cordoba was one of the leading libraries of its time, offering various fields of knowledge, including collections of Islamic and European history. This research aims to understand the development of scientific civilization which became a mecca of progress in Europe during the Second Umayyad Dynasty. This research methodology uses a library research approach with data collection through literature, documentation (both printed and electronic), as well as data and information sources relevant to the study. The findings in this study show that the development of science in Cordoba during the Second Umayyad Dynasty was driven by the construction of academies and libraries. The palace library in Cordoba, built by Caliph Abdurrahman, was one of the best libraries in the Islamic world at the time. It was staffed by a librarian called a